Abnormalities in centrosome number in human embryos and embryonic stem cells. Issue 5 (6th May 2016) - Gu, Yi‐Fan; OuYang, Qi; Dai, Can; Lu, Chang‐Fu; Lin, Ge; Gong, Fei; Lu, Guang‐Xiu
SUMMARY: Chromosomal abnormalities are common in human embryos. Previous studies have suggested links between centrosome number and chromosome abnormalities, but information regarding abnormalities in centrosome number in human embryos is limited. We analyzed abnormalities in centrosome number in human embryos and embryonic stem cells (hESCs). Following normal fertilization, supernumerary centrosomes were present at rates of 7.3% in two‐pronucleus (2PN)‐stage zygotes and 6.5% in first‐cleavage zygotes. Supernumerary centrosomes were also detected in 24.4% of blastomeres from 60% of embryos derived from 2PN zygotes. Conversely, in mono‐ (1PN) and tri‐pronucleus (3PN) zygotes, the frequency of abnormal centrosome number increased substantially at first cleavage. Rates in blastomeres of Day‐3 embryos, however, were about the same between embryos derived from 1PN and 2PN zygotes, whereas abnormalities in centrosome number were higher in those from 3PN zygotes. By comparison, the rate of abnormal centrosome numbers in hESCs was 1.5–11.2%. Thus, abnormalities in centrosome number existed in human zygotes and cleaved embryos—especially those resulting from aberrant fertilization—but the frequency of such abnormalities was lower in hESCs derived from these embryos. These findings identify a source of the chromosomal instability in human embryos and hESCs, and highlight new safety issues for human assisted reproductive technology. Mol. Reprod. Dev. 83: 392–404, 2016. © 2016 Wiley Periodicals, Inc .